Micropulse Laser Trabeculoplasty with 577 nm Wavelength at 1500 or 1000 mW for Primary Open-Angle Glaucoma: A Pilot Study - Tommaso Verdina; Matteo Gironi; Bruno Battaglia; Michele Gentile; Johanna Chester; Shaniko Kaleci; Gianluca Scatigna; Rodolfo Mastropasqua; Gian Maria Cavallini (Life, 2023)
Aim: To investigate the efficacy and safety of micropulse laser trabeculoplasty (MLT) using a 577 nm yellow wavelength laser randomly assigned to either 1500 or 1000 mW in patients with primary open-angle glaucoma (POAG). Methods: A prospective, double-blinded study of POAG patients was performed in a single center. MLT treatment included a 577 nm micropulse laser (IRIDEX IQ 577TM, IRIDEX, Mountain View, CA, USA) to 360° of the trabecular meshwork at randomly assigned varying powers: 1500 mW in one eye (MLT 1500 group) and 1000 mW in the other (MLT 1000 group). Best-corrected visual acuity (BCVA), intraocular pressure (IOP), corneal central thickness (CCT), and endothelial cell count (ECC) were evaluated at baseline (T0), post-operative 1 h (T1), 24 h (T2), 1 month (T3), 3 months (T4), and 6 months (T5) after laser treatment. Topical medications were assessed pre-treatment and at T4. Results: Among the 18 eyes included, we achieved a success rate (IOP reduced > 20%) in 77% of sampled eyes. In particular, IOP reduced at T2 and T3 with both MLT 1500 and 1000 without any significant differences (IOP reduction 22.9% vs. 17.3%, respectively, MLT1500 vs. MLT1000 at T2). The IOP returned to baseline values at T4 and T5 in both groups, with a reduction in topical medications administered from 2.5 ± 1.1 to 2.0 ± 1.2 to the 1500 mW group and from 2.4 ± 1.0 to 1.9 ± 1.0 to the 1000 mW group. At 1 h post-laser treatment, a transient IOP spike was registered among the MLT1500 group. There were no differences in CCT and ECC at any timepoint according to the laser powers. Conclusions: Over a 6-month follow-up period, 577 nm MLT at either 1500 or 1000 mW reduces IOP, enabling a stable reduction in the number of topical medications required for patients treated for POAG without any significant difference in terms of effectiveness and safety.